THE ROLE OF JOB SATISFACTION AND WORK MOTIVATION IN ENHANCING NURSES’ ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Michael Sisko; Farida Yuliaty; Etty Sofia Mariati Asnar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the influence of job satisfaction and work motivation on Organizational Citizenship Behavior (OCB) among nurses. Understanding factors that encourage extra-role behavior is essential in healthcare organizations where teamwork, cooperation, and voluntary contributions significantly affect service quality and organizational effectiveness. This research employed a quantitative approach using a census method involving all 63 nurses as the study population. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple linear regression analysis to determine the relationships and effects among variables. The descriptive findings indicate that job satisfaction, work motivation, and Organizational Citizenship Behavior among nurses are generally in the good category, reflecting positive perceptions toward the work environment and organizational conditions. The regression analysis reveals that both job satisfaction and work motivation positively influence Organizational Citizenship Behavior. Job satisfaction shows a positive effect with a standardized coefficient (β = 0.312), while work motivation demonstrates a stronger influence (β = 0.348), indicating that motivation is the most dominant factor in encouraging nurses to perform extra-role behaviors. Furthermore, the coefficient of determination (R² = 0.710) indicates that 71.0% of the variation in Organizational Citizenship Behavior can be explained jointly by job satisfaction and work motivation, while the remaining 29.0% is influenced by other factors outside the research model. The findings suggest that improving job satisfaction and strengthening work motivation are crucial strategies for encouraging nurses to demonstrate voluntary behaviors that support teamwork and organizational performance. Therefore, healthcare management should continuously develop supportive organizational policies to enhance employee satisfaction and motivation in order to maintain high-quality healthcare services.